Fiction and curatorial practice: developing alternative experiences for digital artistic prototypes. Issue 1 (2nd January 2016) - Arrigoni, Gabriella; Zics, Brigitta
ABSTRACT: Increasingly, digital artworks are developed as part of research endeavours, and respond to a cultural climate which values co-creation, practices of tinkering, re-cycling or re-purposing and innovation. As a consequence, these works tend to be unstable, constantly open to change and to the intervention of possible collaborators. Because of such openness to transformation and their involvement in knowledge production and sharing, they can be considered as prototypes, and generate ne'w opportunities for curatorial practice. This article introduces a curatorial project developed around one such artistic prototype, the Eye Resonator, and based on the idea that audience experience can be structured or transformed by speculatively relating the piece to alternative uses and everyday life contexts, different from its role as an interactive artwork. Our strategy is inspired by design methodologies based on the use of fiction, and imagines scenarios where the technological specificities of the piece can be repurposed. This intervention was partially intended to respond to a series of problems encountered in previous showings of the piece, and aims at scaffolding the participant experience by providing, through the scenarios, additional cultural references and entry keys to approach the prototype.